2014
DOI: 10.1155/2014/724639
|View full text |Cite
|
Sign up to set email alerts
|

Null Steering of Adaptive Beamforming Using Linear Constraint Minimum Variance Assisted by Particle Swarm Optimization, Dynamic Mutated Artificial Immune System, and Gravitational Search Algorithm

Abstract: Linear constraint minimum variance (LCMV) is one of the adaptive beamforming techniques that is commonly applied to cancel interfering signals and steer or produce a strong beam to the desired signal through its computed weight vectors. However, weights computed by LCMV usually are not able to form the radiation beam towards the target user precisely and not good enough to reduce the interference by placing null at the interference sources. It is difficult to improve and optimize the LCMV beamforming technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The best individual of each normal subpopulation will be memorized into the elite subpopulation during the evolution process. Darzi et al [122] incorporated PSO, dynamic mutated AIS (DM-AIS), and gravitational search algorithm (GSA) into the existing LCMV technique in order to improve the weights of LCMV.…”
Section: With Aismentioning
confidence: 99%
“…The best individual of each normal subpopulation will be memorized into the elite subpopulation during the evolution process. Darzi et al [122] incorporated PSO, dynamic mutated AIS (DM-AIS), and gravitational search algorithm (GSA) into the existing LCMV technique in order to improve the weights of LCMV.…”
Section: With Aismentioning
confidence: 99%
“…As a result, measures should be taken to lower the SLL. Previous studies showed that artificial intelligence optimisation algorithms such as genetic algorithms [17], artificial bee colony [18], and particle swarm optimisation [19, 20] were successfully applied to handle a variety of problems in order to improve various issues in the antenna system [21, 22]. However, these methods increase the system complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, to localize the near field targets, the range information must also be incorporated into the signal model along with DOA [3,4]. Near field targets localization, especially 3D (range, elevation angle, and azimuth angle), plays significant role in radar, cognitive radio networks, and array signal processing, since it is a preliminary step for adaptive beamformer to guide the main beam in preferred direction and simultaneously manage the nulls in the direction of jammers [5][6][7].…”
Section: Introductionmentioning
confidence: 99%